PENGAWASAN PELANGGARAN BANGUNAN-BANGUNAN DI KOTA DENPASAR - Permatasari, Indah; Sukihana, Ida Ayu (Kertha Desa; Vol. 01, No. 01, Maret 2013, 2013)
Spatial trespass particularly buildings trespass often occur in Denpasar city. The waythat can be used to solve spatial problems that occur is through supervision.Supervision of spatial is regulated in Article 55 in the Act number 26 of 2007 whichconsists of action monitoring, evaluation and reporting. The first problem that arises iswhat kind of buildings trespass that occurred in Denpasar city, secondly is what kind ofsurveillance efforts were made to minimize trespass of the buildings in Denpasar city.This legal research is empirical legal research using interview data collectiontechnique. The conclusion of the research shows that amount of buildings trespasswhich occurred in Denpasar city is still dominated by high trespass buildings permitand controlled by the relevant institute in the form of monitoring and evaluation, inaddition the community also play an active role in the conduct related to reportingtrespass.
Keywords: buildings trespass, supervision, spartial, monitoring.